2011
DOI: 10.1111/j.1365-2524.2011.01009.x
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study about self-medication in the community among market vendors in Fuzhou, China

Abstract: Despite government efforts to increase health care insurance and access in China, many individuals, regardless of insurance status, continue to engage in high levels of self-medication. To understand the factors influencing common self-medication behaviour in a community of food market venders in Fuzhou China, a total of 30 market venders were randomly recruited from six food markets in 2007. In-depth interviews were conducted with each participant at their market stalls by trained interviewers using a semi-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 40 publications
11
45
0
Order By: Relevance
“…Qualitative data were analyzed using the constant comparative method (Lincoln and Guba, 2000). Early in the data analytic process, findings appeared to corroborate thematic findings of Wen et al (Wen et al, 2011 Table 2.…”
Section: Discussionsupporting
confidence: 71%
“…Qualitative data were analyzed using the constant comparative method (Lincoln and Guba, 2000). Early in the data analytic process, findings appeared to corroborate thematic findings of Wen et al (Wen et al, 2011 Table 2.…”
Section: Discussionsupporting
confidence: 71%
“…28.9% of the participants in Tabiee et al's study (2012) counted the non-riskiness of these drugs as the reason behind their arbitrary drug use. In the study conducted by Wen et al (2011), fast recovery and ease of access to these drugs were counted as the main reason for OTC drug use (33). It appears that the belief in non-riskiness of OTC drug use and having experience in treating illnesses are among the main factors of arbitrary drug use, and it is of great significance to identify and analyze the factors contributing to arbitrary drug use among various groups of society so as to decrease self-medication and its impacts (28).…”
Section: False Self-confidencementioning
confidence: 99%
“…Also, in the study conducted by Wen et al (2011), the main reasons for self-medication were revealed to be lack of the need for visiting doctors for non-serious and minor illnesses such as cold, headache, fever, pain in the body, Indigestion, as well as fast recovery through self-medication (33).…”
Section: False Self-confidencementioning
confidence: 99%
See 1 more Smart Citation
“…Even though the behaviour is noted to save money and time [4,5], it has potential to harm the people [6]. For example, misuse of nonsteroidal anti-inflammatory drugs is potentially noted to cause damage to the gastroduodenal mucosa via several mechanisms [7].…”
Section: Introductionmentioning
confidence: 99%